Pengetahuan 1000 HPK Ibu dan Stunting Balita di Desa Non Prioritas Stunting - Nina Fentiana; Dian Anggreani Nasution; Daniel Ginting (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
Stunting in toddlers is characterized by a shorter height compared to other children of his age. This study aims to identify the relationship between knowledge about the first 1000 days of life in mothers of children under five with stunting under five in non-stunting priority villages (Tanjung Baru Village, Batang Lubu Sutam District, Padang Lawas Regency). Cross sectional research design. The study population was all mothers who had toddlers totaling 146 people and the sample was calculated using the Slovin formula (n = 60) and the sample was taken using accidental sampling. The results showed that 55% of children under five in Tanjung Baru Village were stunted and 61.7% of mothers of children under five had knowledge of 1000 HPK in the low category. The results of the chi square test concluded that there was a relationship between knowledge in the first 1000 days of life with stunting under five in non-stunting priority villages (p<0.005). These findings suggest the handling of stunting in an effort to increase knowledge of 1000 HPK for mothers of children under five through counseling and counseling activities on a regular basis at the posyandu.